Using Multimedia Tools to Enhance Cognitive Engagement: A Comparative Study in Secondary Education - Ida Farida; Isabella Clark (Scientechno: Journal of Science and Technology, 2024)
BackgroundThe integration of multimedia tools in education has become increasingly prevalent, especially in secondary education, as it is believed to enhance cognitive engagement and facilitate deeper learning. However, empirical studies comparing the effectiveness of different multimedia tools in fostering cognitive engagement in secondary education remain limited. This study aims to bridge this gap by evaluating the impact of multimedia tools on cognitive engagement in secondary school classrooms. PurposeThe primary objective of this research is to examine the effects of multimedia tools—such as videos, interactive simulations, and educational games—on students' cognitive engagement. The study compares traditional instructional methods with multimedia-enhanced teaching strategies to assess which approach leads to higher levels of cognitive engagement among secondary school students. MethodA comparative research design was employed, involving two groups of secondary school students. One group received traditional instruction, while the other engaged with multimedia tools during lessons. Data were collected using cognitive engagement scales, classroom observations, and student interviews. ResultsThe findings reveal that students using multimedia tools demonstrated significantly higher levels of cognitive engagement, particularly in tasks requiring problem-solving and critical thinking. Students expressed greater interest and motivation in lessons involving multimedia. ConclusionThe study concludes that multimedia tools effectively enhance cognitive engagement in secondary education. These tools should be incorporated into teaching practices to foster deeper learning and improve student outcomes.